Anthropogenic influences and climate changes in Lake Hazar (eastern Turkey) during the Late Holocene - Biltekin, Demet; Eriş, Kürşad Kadir; Bulut, Selda (Elsevier BV, 2021)
Abstract Palaeoecological reconstruction was carried out at Lake Hazar in eastern Turkey from 3.2 cal ka BP to ~510 cal years BP. To evaluate vegetation and climate changes, palynological and grain size analysis were performed by comparing geochemical data, magnetic susceptibility (MS), and Total Organic Carbon (TOC). A lake level reconstruction has been done by palynological data, indicating local environmental changes at Lake Hazar. The first lake level rise was recorded between 3.2 and 2.9 cal ka BP, showing higher river discharge due to the wetter climate. This is also evidenced by higher values in Ca/Ti and TOC values, in coarser grain size and the abundance of trees (mainly deciduous Quercus), while non-arboreal plants (NAP) decrease in the environs of Lake Hazar. A sharp drop follows this in lake level between 2.9 and 2.2 cal ka BP, evidenced by a higher the Sr/Ca ratio and fine-grained sediment (